EXP-FUCTION METHOD FOR EXACT SOLUTIONS OF SOME NON-LINEAR PARTIAL DIFFERENTIAL EQUATIONS - Ic, Unal (Vinca Inst Nuclear Sci, 2022)
In this study, we have obtained the exact solutions of (2+1) and (3+1)-D constant coefficient KdV equations by applying the exponential function method. These exact solutions we find are in the form of an exponential function. In addition, we have seen that these solutions provide the equations by using MATHEMATICA 11.3 program. Apart from that, we have shown the graphics performance of some of the solutions found.
Keywords: (2+1)-D constant coefficient KdV equation; exact solution; (3+1)-D constant coefficient KdV equation; exponential function method